Національні правові основи репатріації в Україні - Ткач, Дмитро; Tkach, Dmytro (Видавництво Львівської політехніки, 2025)
Стаття присвячена комплексному аналізу національних правових основ репатріа- ції в Україні. Розглянуто сутність поняття “репатріація” у контексті міжнародного та національного законодавства, досліджено нормативно-правову базу, що регулює проце- си повернення громадян України на батьківщину. Проаналізовано основні законодавчі акти, що стосуються правового статусу репатріантів, зокрема Конституцію України, Закон України “Про закордонних українців”, Закон України “Про імміграцію” та інші нормативно-правові документи. Особливу увагу присвячено проблемам реалізації права на репатріацію в умовах військового конфлікту та вимушеного переміщення значної частини населення за кордон. У дослідженні визначено правові механізми сприяння поверненню та реінтеграції громадян України, що перебувають за кордоном, включно із системою державних гарантій, соціального забезпечення та працевлаштування репатріантів. Проаналізовано специфіку застосування правових норм щодо репатріації різних категорій осіб: депор- тованих за національною ознакою, трудових мігрантів, біженців від військових дій. Ви- світлено питання взаємодії національного законодавства з міжнародно-правовими стан- дартами у сфері репатріації та захисту прав репатріантів. На основі аналізу нормативно-правової бази та практики її застосування виявлено прогалини в законодавчому регулюванні процесів репатріації та запропоновано шляхи вдосконалення правового механізму репатріації в Україні. Обґрунтовано потребу роз- робки та прийняття спеціального закону, що комплексно регулюватиме питання репат- ріації громадян України, з урахуванням сучасних викликів, зумовлених масовою мігра- цією внаслідок військового конфлікту. Сформульовано практичні рекомендації щодо вдосконалення правового забезпечення процесів репатріації та посилення захисту прав репатріантів у контексті нової міграційної політики України.

The article is dedicated to a comprehensive analysis of the national legal frameworks of repatriation in Ukraine. It examines the essence of the concept of “repatriation” within the context of international and national legislation, explores the regulatory framework governing the processes of returning Ukrainian citizens to their homeland, and analyzes key legislative acts related to the legal status of repatriates, including the Constitution of Ukraine, the Law of Ukraine “On Foreign Ukrainians”, the Law of Ukraine “On Immigration”, and other legal documents. Special attention is paid to the challenges of implementing the right to repatriation amid military conflict and the forced displacement of a significant portion of the population abroad. The study identifies legal mechanisms to facilitate the return and reintegration of Ukrainian citizens residing abroad, including systems of state guarantees, social security, and employment for repatriates. It analyzes the specifics of applying legal norms on repatriation to various categories of individuals: those deported on ethnic grounds, labor migrants, and refugees fleeing war. The interaction between national legislation and international legal standards in the field of repatriation and the protection of repatriates’ rights is also highlighted. Based on an analysis of the legal framework and its practical application, the study identifies gaps in the legislative regulation of repatriation processes and proposes ways to improve Ukraine’s legal mechanisms for repatriation. The necessity of developing and adopting a special law that comprehensively regulates the repatriation of Ukrainian citizens is justified, taking into account modern challenges caused by mass migration resulting from military conflict. Practical recommendations are formulated to enhance the legal framework for repatriation processes and strengthen the protection of repatriates’ rights within the context of Ukraine’s new migration policy.
National legal frameworks of repatriation in Ukraine
Keywords: репатріація; національне законодавство; правовий статус репа- тріантів; міграційна політика; права мігрантів; вимушена міграція; повернення громадян; repatriation; national legislation; legal status of repatriates; migration policy; migrants’ rights; forced migration; return of citizens; 34; 94(477)